Perceptual Broadening Leads to More Prosociality - Mukherjee, Sumitava; Srinivasan, Narayanan; Kumar, Neeraj; Manjaly, Jaison A. (Frontiers in Psychology, 2018)
A link between perceptual processing styles and (pro)social behavior has gathered supporting em-pirical evidence to show that people raised or trained in traditions of collectiveness, compassion and prosocial beliefs are biased to the global level in perceptual processing. In this research, we studied the reciprocal link - whether contextually broadening perceptual scope of attention via global pro-cessing could make people more prosocial. We hypothesized that global processing linked previ-ously to an interdependent compassionate self-orientation would make people more prosocial, com-pared to local processing. Four experiments manipulated perceptual scope through a Global-Local task using hierarchical stimuli. It was found that participants who performed a global processing perceptual task volunteered to donate more money across different donation frames, compared to those who performed a local processing task. While previous research showed prosocial mindsets lead to perceptual broadening, the current results suggest that perceptual broadening also leads to more prosociality, thus establishing a reciprocal link between perceptual broadening (attentional scope) and acting prosocially. It is proposed that perceptual scope of attention is one of the generic cognitive processes that underlie prosocial decisions could be perceptual scope of attention. Expla-nations based on scope of attention can potentially be used as a framework that enables researchers to link the effects of different contextual cues on prosocial decisions.